Endoscopic ultrasound-guided biliary drainage of malignant stenosis, not treatable with endoscopic retrograde cholangiopancreatography: a single-center, prospective observational study - Tarantino, Ilaria; Peralta, Marco; Ligresti, Dario; Amata, Michele; Barresi, Luca; Cipolletta, Fabio; Antonio, Granata; Traina, Mario (Endoscopy International Open, 2021)
Background and study aims The therapeutic role of endoscopic ultrasound (EUS) evolved in recent decade,s opening a new chapter in the field of endoscopic biliary drainage (BD). EUS-BD has emerged as a new mini-invasive technique for neoplastic jaundice not amenable to endoscopic retrograde cholangiopancreatography (ERCP). The primary study aims were to assess the clinical efficacy of EUS-BD using an electrocautery-enhanced lumen apposing metal stent (ECE-LAMS) in patients with malignant biliary obstruction with failed\unfeasible ERCP and the adverse event (AE) rate. The secondary aims were to evaluate the technical success and incidence of jaundice recurrence.Patients and methods Data from All patients referred to our tertiary-care Institute with obstructive jaundice due to unresectable malignant distal biliary stricture and unfeasible\failed ERCP, were prospectively recorded from January 2015 to February 2018. The procedures were performed by a single-step ECE-LAMS (AXIOS-EC, Boston Scientific) placement, from the upper gut lumen to the biliary tree, for definitive biliary decompression.Results Twenty-one patients were consecutively enrolled. Mean pre-procedure common bile duct diameter was 16 mm and the bilirubin level was 13.9 mg/dL (range 3.8–29.5). LAMS was positioned from the duodenal bulb (n = 19) to gastric antrum (n = 2). We registered a 100 % of technical and clinical success. No AEs occurred. We observed a single case of delayed AE consisting of a buried LAMS, which was successfully resolved endoscopically.Conclusions Despite the limits of being non-comparative, our study shows outcomes in a homogeneous population in terms of indications and technique. EUS-BD with dedicated ECE-LAMS is associated with extremely good clinical efficacy and safety and can be considered as an alternative in cases of failed/unfeasible ERCP.